블록체인 기반 가상화폐 거래의 보안 위험 및 대응방안 - 정용식(Young-Seek Chung); 차재상(Jae-Sang Cha) (한국정보전자통신기술학회 논문지, 2018)
Since the concept of virtual currency called Bitcoin was announced in 2008, the blockchain technology, which is the basis of Bitcoin, is attracting attention as an important platform technology in the era of the 4th industrial revolution that can change our society in the future. Although Existing electronic financial transactions store and manage all transaction history at a reliable central organization such as government and bank, blockchain-based electronic financial transactions are composed of a distributed structure in which all participants participating in the transaction store and manage the transaction history, it is possible to secure transaction transparency while reducing system construction and operation costs. Besides the virtual currency that started with bit coins, the technology of these blockchains has been extended in various fields such as smart contracts and document management. The key technology area of this blockchain is security based on proven cryptographic technology to make it difficult to forge and hack, but there are security risks such as security vulnerabilities in the virtual currency trading service, We will discuss security risks in using virtual currency and discuss countermeasures. Especially security accidents of virtual currency exchanges are occurring frequently recently, the damage of users who trade the virtual currency is also increasing, we propose security threats and security countermeasures against virtual currency exchanges. 2008년 비트코인이라는 가상화폐의 개념이 발표된 이후, 비트코인의 기반이 되는 블록체인 기술은 향후 우리 사회를 변화시킬 수 있는 4차 산업혁명 시대의 중요한 플랫폼 기술로 주목받고 있다. 기존의 전자금융거래는 정부나 은행 등 신뢰할 수 있는 중앙기관에서 모든 거래 내역을 저장, 관리하고 있는 반면, 블록체인 기반의 전자금융거래는 거래에 참여하는 모든 참여자가 거래 내역을 각각 저장, 관리하는 분산 구조로 이루어져 있어서, 시스템 구축과 운영비용을 절감하면서도 거래의 투명성을 보장할 수 있는 특징을 가지고 있다. 이러한 블록체인 기술은 비트코인으로 시작된 가상화폐 이외에도 스마트 계약, 문서관리 등 다양한 영역으로 그 활용방안이 확장되고 있다. 블록체인의 핵심 기술 영역은 검증된 암호기술을 기반으로 거래 내역의 위조나 해킹이 어렵도록 일정수준 이상의 보안성을 갖추고 있으나, 가상화폐를 사고파는 거래 서비스나 상품 대금으로 지급하는 결제 서비스의 구현에 있어서는 구현 방식에서의 보안 취약점이 존재할 수 있기에 가상화폐 사용에 있어서 보안 위험에 대해서 살펴보고 대응방안에 대해서 논하고자 한다. 특히 가상화폐 거래를 손쉽게 해주는 가상화폐 거래소에 대한 보안 사고가 최근에 자주 발생하고 있으며, 가상화폐를 거래하는 사용자들의 피해도 증가하고 있기에 금융권에 적용 가능한 블록체인 보안 위협을 살펴보고 그 중에서도 특히 보안사고로 인한 피해가 많이 발생하는 가상화폐 거래소에 대한 보안 위협과 적용 가능한 보안 대책을 제시하고자 한다.